THE MEANING OFCOMPETITION IN THE VOICE OF ELDERS IN MASTER SWIMMING. A STUDY ON A VIEW OF A GENDER. (Fiep Bulletin - online, 2015)
The objective of this research was to analyze and interpret the masters´ swimmers speech about practicing competitive swimming on the view of the gender. 12 swimmers participated in which 6 male swimmers and 6 female with the age between 60 and 89 all are enrolled in the Brazilian Master Swimming Association  ABMN in many Brazilian states. As a tool they participated in a semi structured interview about what does it mean to compete. A daily journal was also used. This data was collected during 3 championships in national and international levels which occurred in different stated in Brazil. The answers were reported to the analyses of (ORLANDI, 2000) speed. The results that were analyzed and appointed to self-appreciation of these elders, that implies in a high self esteem. The information also showed that men are concerned of physical appearance As for women, gave very little importance for this matter. They were concerned in health aspects. On the gender's view,  there are evidence that the stereotype related to an old retired man is being broken. The swimmers associate social conviviality of the master group to fraternity, to friendship, to trips as a way to feel good in this stage of life. It's concluded that the people who were interviewed, reject the image of the old people ignored by society, and that competitive swimming is presented to be a factor of improvement besides being a factor of socialization and integration among them.
Keywords: Elders - Self Esteem - Gender